PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP CORPORATE SOCIAL RESPONSIBILITY MELALUI RISIKO BISNIS DAN KINERJA KEUANGAN PADA BANK UMUM SYARIAH DI INDONESIA - Ahmad Roziq; Herdian Nisar Danurwenda (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2012)
This study aims to examine the influence of Good Corporate Governance (GCG) of Corporate Social Responsibility (CSR) with the financial performance and business risk as intervening variable in Indonesian Islamic Bank. The study uses secondary data from GCG report, financial report, and annual report of Indonesian Islamic Bank in the period 2007-2010. The sample in this study is 15 Islamic Banks in Indonesia. The Hypothesis are tested by the Partial Least Square (PLS) approach. The results suggest that the GCG significantly has positive effect on CSR Islamic Bank. GCG significantly has positive effect on the financial performance of Islamic Bank. GCG significantly has positive effect on the business risk of Islamic Bank. However, the financial performance has no effect on the CSR of Islamic Bank and business risk has no effect on the financial performance of Islamic Bank. This suggests that financial performance is not an intervening variable of the effect GCG on the CSR of Islamic Bank and business risk is not an intervening variable of the effect GCG on the financial performance of Islamic Bank. Keywords: Good Corporate Governance, Corporate Social Responsibility, financial performance, business risk, Islamic Bank